Identify, Explain and Prioritize Human Resource Planning Factors in Order to Show Organizational Citizenship Behavior by Employees - Asghari, Elham; Haghighi, Masoud; Vadadi, Ahmad (Iranian Journal of Educational Sociology, 2022)
Purpose: Considering the importance of human resource planning for organizational citizenship behavior, the purpose of this study was identify, explain and prioritize human resource planning factors in order to occurrence organizational citizenship behavior by employees.Methodology: The present research was descriptive from type of qualitative-quantitative. The research population in the qualitative part was documents and texts related to the research and experts were familiar with the subject who tried to identify and explain the factors of human resource planning in order to occurrence organizational citizenship behavior and in the quantitative part were the experts who prioritized these factors. The research sample consisted of 20 research-related documents and 15 experts who were selected by purposive non-random sampling method. Data collection tools included taking notes of documents and texts and surveying about new effective factors and expressing the rate of importance of existing factors in Delphi. Data were analyzed by coding and factor analysis methods.Findings: Findings showed that for the human resource planning pattern in order to occurrence organizational citizenship behavior by employees in the human resource planning part were identified 67 indicators in 19 components and in the organizational citizenship behavior part were identified 28 indicators in 6 components. In human resource planning the 19 components respectively were include performance management, labor adjustment, organizational culture, strategic goals, organizational structure, human resource planning, recruitment, training and development, maintenance, external environment, supply, demand, human resource strategy, strategic planning, management style, flexibility, reward system, job analysis and individual factors and in organizational citizenship behavior the 6 components respectively were include altruism, work conscience, personal development, organizational loyalty, organizational obedience and citizenship virtue.Conclusion: According to the reported results, to develop the occurrence of organizational citizenship behavior by employees can be action through its effective human resource planning factors that was identified in the present research.